ANALYSIS OF THE DEVELOPMENT STATE AND FACTORS OF THE SERVICE INDUSTRY IN THE REPUBLIC OF KARAKALPAKISTAN: https://doi.org/10.5281/zenodo.14235665 - Zarikeyeva , M.M.; Matkarimova , D.A.; Uzakbergenov , S.K.; Bayniyazova, D (International scientific and practical conference, 2024)
At the current stage of the economic development of our country, high demands are placed on the quantity and quality of services. The implementation of the experience of leading foreign countries ensures the growth of demand for services. To increase economic efficiency in service enterprises, to create certain organizational and economic conditions to increase the quality and competitiveness of services by modernizing and diversifying modern branches of the industry, to increase the level of population employment, to form consumer demand for services and fully satisfy their needs, based on modern, digital technologies development of service networks is one of the important issues. Therefore, the article discusses the analysis and factors of the development of the service industry.